2015
DOI: 10.1890/14-1663.1
|View full text |Cite
|
Sign up to set email alerts
|

Tainted resurrection: metal pollution is linked with reduced hatching and high juvenile mortality in Daphnia egg banks

Abstract: Many taxa, from plants to zooplankton, produce long-lasting dormant propagules capable of temporal dispersal. In some cases, propagules can persist for decades or even centuries before emerging from seed and egg banks. Despite impressive longevity, relatively little is known about how the chemical environment experienced before or during dormancy affects the fate and performance of individuals. This study examines the hatching rate and developmental success of Daphnia hatched from diapausing eggs isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Thus, the question arises whether the pattern of investment in diapause observed in our experiments is optimum in an environment with arsenic, or if rather arsenic presence in water bodies disturbs the optimal allocation of offspring going into diapause. Heavy metal concentration in general and arsenic concentration in particular, may produce selective pressure on rotifer populations, as has been suggested from Daphnia egg banks in historically metal polluted sediments (Rogalski 2015). First, volcanic, geothermal activity, in conjunction with evapo-concentration in arid zones should have an effect on environmental concentration of arsenic; Table 3 Starting of the diapausing egg production and total diapausing egg production by B. calyciflorus exposed to medium control and with As 2 O 3 (20 lg L -1 ), with low (0.5 9 10 6 cells mL -1 ) and high (2.5 9 10 6 cells mL -1 ) density of microalga P. subcapitata as food.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, the question arises whether the pattern of investment in diapause observed in our experiments is optimum in an environment with arsenic, or if rather arsenic presence in water bodies disturbs the optimal allocation of offspring going into diapause. Heavy metal concentration in general and arsenic concentration in particular, may produce selective pressure on rotifer populations, as has been suggested from Daphnia egg banks in historically metal polluted sediments (Rogalski 2015). First, volcanic, geothermal activity, in conjunction with evapo-concentration in arid zones should have an effect on environmental concentration of arsenic; Table 3 Starting of the diapausing egg production and total diapausing egg production by B. calyciflorus exposed to medium control and with As 2 O 3 (20 lg L -1 ), with low (0.5 9 10 6 cells mL -1 ) and high (2.5 9 10 6 cells mL -1 ) density of microalga P. subcapitata as food.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, effects of pesticides and sedimentary metals have been observed on development and hatching success of the diapausing eggs of cladocerans Daphnia (Navis et al 2013(Navis et al , 2015Rogalski 2015). Additionally, a field study showed metals were accumulated by Daphnia ephippia (Wyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If Pb toxicity is similarly affected, the selection for Pb resistance inferred in our relatively hard‐water lakes may have been even more pronounced in soft water lakes. Additionally, aside from selection on the free‐swimming life stages, metal pollution has been found to decrease egg hatching rates and juvenile survivorship (Rogalski ). As our study lakes are, at least partly, repopulated every spring from the egg bank, selection on hatching success could provide a strong force for the acquisition of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these dormant propagules as a study system to look at temporal changes in genetic and ecological features of populations (and even communities) has been gaining considerable ground over the past 20-30 years (e.g., Cousyn et al, 2001;Decaestecker et al, 2007;Frisch et al, 2014Frisch et al, , 2017Geerts et al, 2015;Hairston & De Stasio, 1988;Hairston, Van Brunt, Kearns, & Engstrom, 1995;Hairston et al, 1999Hairston et al, , 2001Härnström, Ellegaard, Andersen, & Godhe, 2011;Kerfoot et al, 1999;Levin, 1990;McGraw, 1993;Rogalski, 2015Rogalski, , 2017Vavrek, McGraw, & Bennington, 1991;Weider, Lampert, Wessels, Colbourne, & Limburg, 1997), building on earlier theoretical and empirical work on the evolutionary dynamics of seed banks (e.g., Templeton & Levin, 1979). We believe it is time to bring this emerging field of RE to a broader audience, which includes researchers, scientists, and general public stakeholders who are in- evolutionary medicine-studying "resurrected" microbes and their impacts on modern populations of humans and other species (e.g., the plague, anthrax, smallpox); (v) "dispersal from the past"-with climate/environmental change, how might "natural" dispersal from the past (e.g., melting of ice sheets/glaciers, thawing of permafrost, releasing long-dormant cysts and propagules) impact evolutionary trajectories of modern populations.…”
Section: Overview Of Resurrection Ecology (Re): What Is It?mentioning
confidence: 99%